Regulation of Sucrose Metabolism in Higher Plants: Localization and regulation of Activity of Key Enzymes - Winter, H.; Huber, S.C.
Sucrose (Suc)plays a central role in plant growth and development. It is a major end product of photosynthesis and functions as a primary transport sugar and in some cases as a direct or indirect regulator of gene expression. Research during the last 2 decades has identified the pathways involved and which enzymes contribute to the control of flux. Availability of metabolites for Suc synthesis and 'demand' for products of sucrose degradation are important factors, but this review specifically focuses on the biosynthetic enzyme sucrose-phosphate synthase (SPS), and the degradative enzymes, sucrose synthase (SuSy), and the invertases. Recent progress has included the cloning of genes encoding these enzymes and the elucidation of posttranslational regulatory mechanisms. Protein phosphorylation is emerging as an important mechanism controlling SPS activity in response to various environmental and endogenous signals. In terms of Suc degradation, invertase-catalyzed hydrolysis generally has been associated with cell expansion, whereas SuSy-catalyzed metabolism has been linked with biosynthetic processes (e.g., cell wall or storage products). Recent results indicate that SuSy may be localized in multiple cellular compartments: (1)as a soluble enzyme in the cytosol (as traditionally assumed); (2)associated with the plasma membrane; and (3)associated with the actin cytoskeleton. Phosphorylation of SuSy has been shown to occur and may be one of the factors controlling localization of the enzyme. The purpose of this review is to summarize some of the recent developments relating to regulation of activity and localization of key enzymes involved in sucrose metabolism in plants.
Keywords: ACTIN CYTOSKELETON; 14-3-3 PROTEINS; INVERTASE; SNF1 PROTEIN KINASE; CDPK; REGULATORY PROTEIN PHOSPHORYLATION; SUCROSE-PHOSPHATE SYNTHASE; SUCROSE-SENSING; SUCROSE SYNTHASE; TRANSLOCATION